2014
DOI: 10.1371/journal.pone.0092736
|View full text |Cite
|
Sign up to set email alerts
|

Gait Initiation in Children with Rett Syndrome

Abstract: Rett syndrome is an X-linked neurodevelopmental condition mainly characterized by loss of spoken language and a regression of purposeful hand use, with the development of distinctive hand stereotypies, and gait abnormalities. Gait initiation is the transition from quiet stance to steady-state condition of walking. The associated motor program seems to be centrally mediated and includes preparatory adjustments prior to any apparent voluntary movement of the lower limbs. Anticipatory postural adjustments contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 31 publications
(43 reference statements)
2
21
0
1
Order By: Relevance
“…A systematic survey by Ledebt et al (1998) [15] showed that APAs start developing at 2-3 years of age but complete their maturation well after the age of 8, a result in line with the observations carried out on toddlers up to 5 years old children [16] and in 4-6 years old children [17]. Another interesting study was published by Isaias et al (2014) [18], who analyzed SOL and TA in 10 ± 3 years-old children and reported inhibition-excitation patterns like in adults, but with a lower time interval between SOL inhibition and TA excitation.…”
Section: Introductionsupporting
confidence: 72%
“…A systematic survey by Ledebt et al (1998) [15] showed that APAs start developing at 2-3 years of age but complete their maturation well after the age of 8, a result in line with the observations carried out on toddlers up to 5 years old children [16] and in 4-6 years old children [17]. Another interesting study was published by Isaias et al (2014) [18], who analyzed SOL and TA in 10 ± 3 years-old children and reported inhibition-excitation patterns like in adults, but with a lower time interval between SOL inhibition and TA excitation.…”
Section: Introductionsupporting
confidence: 72%
“…El RTT es una enfermedad compleja y de difícil diagnóstico debido a la gran variedad de manifestaciones clínicas que puede generar y su rara presentación en la población. Ya que no se encontraron caracterizaciones moleculares en Latinoamérica y las series de casos reportadas en la literatura internacional suelen poseer pocas participantes y diferentes mutaciones, no es posible confirmar la relación directa de una mutación con determinada presentación clínica (5,71,72). Teniendo eso en cuenta, se resumen las características de las pacientes y sus diagnósticos moleculares en la tabla 4 y se comparan con las descritas por mutaciones en las bases de datos de LOVD, RettBASE, Francia y Estados Unidos (27,60).…”
Section: Discussionunclassified
“…There is also a correlation between the presence of scoliosis and walking impairment; in the study by Downs et al, scoliosis had been diagnosed in 86% of females who were unable to walk. Even when present, walking shows some peculiar patterns due to ataxia, lack of core stability, and lack of feed‐forward control of movement at gait initiation . Longitudinal studies evaluating motor development in RTT mainly use questionnaires and analysis of videotapes.…”
mentioning
confidence: 99%
“…Even when present, walking shows some peculiar patterns due to ataxia, lack of core stability, and lack of feed-forward control of movement at gait initiation. 9 Longitudinal studies evaluating motor development in RTT mainly use questionnaires and analysis of videotapes. Video-recorded sessions assessed by expert clinicians are not easily available, owing to the rarity of the disease and the geographical dispersion of patients.…”
mentioning
confidence: 99%